Accommodation Tax In The City Of Košice: Initial Stage Of Research - Vartašová, Anna; Červená, Karolína (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: The authors focused on one of the local taxes in Slovakia, namely the accommodation tax, which represents a source of own income for Slovak municipalities. Although its budgetary importance is not significant from a national perspective, it is important from the perspective of the budgets of individual cities. Despite this, there is a lack of comprehensive research on this tax as a source of income, which represents a research gap within the Slovak Republic. Aim: The aim of the article is to identify the trend in accommodation tax revenues from 2010 to 2023 at a selected local level (city of Košice), thereby confirming the assumption of the growing importance of that revenue, as well as identifying possible influencing factors. Results: The results of our research showed that the potential of the tax as a source of income for municipalities has not yet been fully utilized - which is an argument for the justification of further research. The following legislative factors influencing the income from this tax were identified: the method of determining the tax rate, the scope of exempt overnight stays, the possibility of transferring the collection of the tax from the accommodation provider to digital platforms as accommodation intermediaries, and as non-legislative factors, the ability of the city to control tax obligations and the city's policy in the field of tourism development (increasing the attractiveness of the city as a tourist destination), while the significance and correlation of the above factors will be the subject of further follow-up research. An interesting result of the research is also the identification of discrepancies between the available data of the Statistical Office of the Slovak Republic and data from the regional database (city of Košice) due to the application of different reporting methodologies, which may result in a distortion of the actual situation or statistically differentiated results.